Katherine Arens. Vienna’s Dreams of Europe: Culture and Identity Beyond the Nation-State. New York: Bloomsbury, 2015. - Nathaniel Parker Weston (Studies in 20th & 21st Century Literature, 2017)
Review of Katherine Arens. Vienna’s Dreams of Europe: Culture and Identity Beyond the Nation-State. New York: Bloomsbury, 2015.
Keywords: Book Review; Katherine Arens; Vienna’s Dreams of Europe: Culture and Identity Beyond the Nation-State